Platform Trial Designs in Drug Development : Umbrella Trials and Basket Trials - Antonijevic, Zoran; Beckman, Robert A.; Taylor and Francis (Boca Raton, FL : Chapman and Hall/CRC, 2018)
Platform trials test multiple therapies in one indication, one therapy for multiple indications, or both. These novel clinical trial designs can dramatically increase the cost-effectiveness of drug development, leading to life-altering medicines for people suffering from serious illnesses, possibly at lower cost. Currently, the cost of drug development is unsustainable. Furthermore, there are particular problems in rare diseases and small biomarker defined subsets in oncology, where the required sample sizes for traditional clinical trial designs may not be feasible. The editors recruited the key innovators in this domain. The 20 articles discuss trial designs from perspectives as diverse as quantum computing, patient$1 (Bs rights to information, and international health. The book begins with an overview of platform trials from multiple perspectives. It then describes impacts of platform trials on the pharmaceutical industry$1 (Bs key stakeholders: patients, regulators, and payers. Next it provides advanced statistical methods that address multiple aspects of platform trials, before concluding with a pharmaceutical executive$1 (Bs perspective on platform trials. Except for the statistical methods section, only a basic qualitative knowledge of clinical trials is needed to appreciate the important concepts and novel ideas presented.s
Contents -- Preface .ix -- Acknowledgments . xiii -- List of Contributors .xv -- Part I Overview of Platform Clinical Trials. . 1 -- 1 I-SPY2: Unlocking the Potential of the Platform Trial. . . .3 -- Laura Esserman, Nola Hylton, Smita Asare, Christina Yau, -- Doug Yee, Angie Demichele, Jane Perlmutter, Fraser Symmans, -- Laura vant Veer, Jeff Matthews, Donald A. Berry, and Anna Barker -- 2 The Challenges with Multi-Arm Targeted Therapy Trials. .23 -- Ryan J. Sullivan and Keith T. Flaherty -- 3 Basket Trials at the Confirmatory Stage... .37 -- Robert A. Beckman and Cong Chen -- 4 Harnessing Real-World Data to Inform Platform -- Trial Design . . .55 -- Daphne Guinn, Subha Madhavan, and Robert A. Beckman -- 5 Impact of Platform Trials on Pharmaceutical Frameworks. .73 -- Zoran Antonijevic, Ed Mills, Jonas Hggstrm, and -- Kristian Thorlund -- Part II Stakeholders...83 -- 6 Friends of Cancer Research Perspective on Platform Trials.85 -- Jeffrey D. Allen, Madison Wempe, Ryan Hohman, and Ellen V. Sigal -- 7 Regulatory and Policy Aspects of Platform Trials..97 -- Rasika Kalamegham, Ramzi Dagher, and Peter Honig -- 8 Multi-Arm, Multi-Drug Trials from a Reimbursement -- Perspective . . .119 -- Anja Schiel and Olivier Collignon -- 9 Highly Efficient Clinical Trials: A Resource-Saving Solution -- for Global Health 125 -- Edward J. Mills, Jonas Hggstrm, and Kristian Thorlund -- 10 Decision Analysis from the Perspectives of Single and -- Multiple Stakeholders.....141 -- Robert A. Beckman, Carl-Fredrik Burman, Cong Chen, -- Sebastian Jobjrnsson, Franz Knig, Nigel Stallard, and -- Martin Posch -- 11 Optimal Approach for Addressing Multiple Stakeholders -- Requirements in Drug Development... . 153 -- Zoran Antonijevic and Zhongshen Wang -- Part III StatisticalMethodology... . 165 -- 12 Primary Site Independent Clinical Trials in Oncology. . . 167 -- Richard M. Simon -- 13 Platform Trials . 181 -- Ben Saville and Scott Berry -- 14 Efficiencies of Platform Trials.... 197 -- Satrajit Roychoudhury and Ohad Amit -- 15 Control of Type I Error for Confirmatory Basket Trials. . 211 -- Cong Chen and Robert A. Beckman -- 16 Benefit-Risk Assessment for Platform Trials... . 231 -- Chunlei Ke and Qi Jiang -- 17 Effect of Randomization Schemes in Umbrella Trials -- When There Are Unknown Interactions between -- Biomarkers253 -- Janet J. Li, Shuai Sammy Yuan, and Robert A. Beckman -- 18 Combinatorial and Model-Based Methods in Structuring -- and Optimizing Cluster Trials.... 265 -- Valerii V. Fedorov and Sergei L. Leonov -- Part IV Conclusions...287 -- 19 An Executives View of Value of Platform Trials.. 289 -- David Reese and Phuong Khanh Morrow -- Index. . . .295.
Includes bibliographical references and index.
Also available in print format.
Keywords: MEDICAL / Pharmacology; MEDICAL / Biostatistics; Drugs -- Testing; Clinical trials; Electronic books